A wearable system for monitoring the velocity variability in open water swimming and triathlon - Dadashi, F.; Millet, G.; Aminian, K. (2013)
Pacing tactics in the swimming bout notably influences the overall triathlon performance. Besides, the swimming velocity affects the energy expenditure (EE). Based on our previous works to estimate the swimming velocity, here we propose a system to measure the cycle velocity variation (CVV) (important factor that governs the swimming EE) using one body-worn inertial measurement unit (IMU). We have previously shown that our system is capable of measuring cycle mean velocity (CMV) with an RMS error of 9.0 cm/s.